2017
DOI: 10.1016/j.vetmic.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of three genetically diverse strains of PRRSV Type 1 in specific pathogen free pigs

Abstract: Studies from Eastern European countries proved that porcine reproductive and respiratory syndrome virus Type 1 (PRRSV-1) harbours high genetic diversity and that genetically divergent subtypes 2-4 circulate in this area. In the present study, we compared the pathogenicity of two different PRRSV-1 subtype 2 strains and a strain representing PRRSV-1 subtype 1. Four groups of 8-week-old specific pathogen free pigs were either infected with subtype 2 strain ILI6, subtype 2 strain or BOR59, subtype 1 strain 18794, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 45 publications
6
42
1
1
Order By: Relevance
“…an animal that become positive after being tested negative. The duration of nasal excretion of PRRSV was in line with the previous studies quoted above (7)(8)(9)(10)(11)(12)(13)(14). There is probably a limited risk that these weakly positive animals would transmit the virus horizontally to naïve animals [21], but the persistence of vaccine virus for two-three months after vaccination emphasize the importance of keeping vaccinated animals isolated from naïve animals for a sustained time period prior to mingling.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…an animal that become positive after being tested negative. The duration of nasal excretion of PRRSV was in line with the previous studies quoted above (7)(8)(9)(10)(11)(12)(13)(14). There is probably a limited risk that these weakly positive animals would transmit the virus horizontally to naïve animals [21], but the persistence of vaccine virus for two-three months after vaccination emphasize the importance of keeping vaccinated animals isolated from naïve animals for a sustained time period prior to mingling.…”
Section: Discussionsupporting
confidence: 84%
“…Only few studies have been performed with these diverse East-European strains, but a series of studies have revealed that at least some subtype 3 strains are more virulent than typical subtype 1 strains [35][36][37][38]. Recently, we have shown that some subtype 2 strains seem to be more virulent than subtype 1 strains [10] and in both the previous and the present study ILI6 induced more severe clinical signs and more pronounced viremia than the PRRSV-1, subtype 1 strains. Nevertheless, the clinical signs were much less severe than seen following challenge with the two subtype 3 strains SU-1 and Lena [35,36].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations